On the relation between managerial power and CEO pay - Göx, Robert F.; Hemmer, Thomas (Journal of Accounting and Economics, 2020)
We study how friendly boards design the structure of optimal compensation contracts in favor of powerful CEOs. Our study yields unexpected results. First, powerful managers receive higher pay and a contract with a higher pay-performance sensitivity (PPS) if firm performance is low and vice versa. Moreover, we identify conditions where expected pay and expected PPS are both increasing in the friendliness of the board. Second, we show that friendly boards provide managers with higher salaries, more shares, but less options. Third, friendly boards offering contracts with a higher PPS also make more intensive use of relative performance evaluation (RPE). Overall, our results suggest that frequently used indicators of poor (or sound) compensation practices should be interpreted with care. Extending the scope of our model beyond executive pay, we show that powerful managers underinvest in capital but have less incentives to manage earnings.